Pembentukan Hukum dan Prinsip Syariah dalam Perdagangan Cryptocurrency - Kusuma Atmaja, Muhammad Noval; Sujianto, Agus Eko; Ni’mah, Zulfatun (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Cryptocurrency has become one of the technological innovations that is changing the paradigm of the global financial system. However, in the context of Islamic law, the legality of cryptocurrency trading still applies. This article aims to analyze sharia principles relevant to cryptocurrencies and explore their potential application in the Islamic finance ecosystem. Using a normative approach and literature study, this article finds that the halalness of cryptocurrency depends on aspects of gharar (uncertainty), usury, and general usefulness. This article also recommends a regulatory framework for the development of Islamic cryptocurrencies.